Pengaruh Ajaran Tarekat Tijaniyah terhadap Peningkatan ESQ (Emotional Spiritual Quotient) Jamaah PP. Syubbanul Ummah Al Abidin Lamongan - Ulul Miya Saroh; Umi Chaidaroh (Universitas KH. A. Wahab Hasbullah, 2019)
The development of modern era and rapid technological advances, not only impacting positively to the community but also gives negative impact of emotional and spiritual crisis. People are always deep in their love towards the world, and makes material the benchmark of everything and not having a grip on life. Therefore human beings must strive to improve the emotional and spiritual quotient or known as ESQ, one of which is through the teachings of the Order of Tijaniyyah, in which the congregation does not only obtain the fulfillment of his spiritual side alone, but also from his emotional side. The purpose of this research is to describe the doctrine of Tijaniyyah and ESQ in the boarding school Syubbanul Ummah Al Abidin, and to analyze the presence or absence of the influence of the doctrine of Tijaniyyah to the increase of ESQ pilgrims in the boarding school Syubbanul Ummah Al Abidin. The research approach used is a quantitative approach with statistical data analysis for predefined hypothesis testing. This research gives the results that the doctrine of Tijaniyyah and ESQ worshippers are on high criteria. As well as the rcount (0.745) > rtable (0.279). So Ha is accepted which means there are influences of the doctrine of Tijaniyyah to the increase of ESQ (Emotional Spiritual Quotient) worshippers in the boarding school Syubbanul Ummah Al Abidin Sumbergondang Bluluk of Lamongan which amounted to 56%.